Potensi Biochar sebagai Media Pembawa Bakteri Halotoleran untuk Meningkatkan Kesuburan Tanah Salin: Review Literatur: The Potential of Biochar as a Carrier Medium for Halotolerant Bacteria to Improve Saline Soil Fertility: A Literature Review - Dewi, Dora Silvia; Zulfida, Ida; Windani, Isna (Jurnal Riset Agribisnis dan Peternakan, 2026)
Soil salinization is one of the major limiting factors in agricultural production because it deteriorates the physical, chemical, and biological properties of soil and inhibits plant growth. This article aims to review the potential of biochar as a carrier medium for halotolerant bacteria to improve the fertility of saline soils through a narrative literature review approach. The review examines scientific publications related to the characteristics of saline soils, the mechanisms of halotolerant bacteria, the properties of biochar as a soil ameliorant and microbial carrier, and the synergistic interaction between biochar and bacteria in the soil– plant system. The findings indicate that halotolerant bacteria enhance plant tolerance to salinity stress through the production of phytohormones, exopolysaccharides, ACC deaminase, osmoprotectants, phosphate solubilization, nutrient mobilization, and ionic homeostasis regulation. Meanwhile, biochar has high porosity, large surface area, water-holding capacity, cation exchange capacity, and surface functional groups that support microbial viability, adhesion, biofilm formation, and colonization. The combination of biochar and halotolerant bacteria has the potential to generate synergistic effects by improving soil structure, increasing water and nutrient retention, reducing sodicity impacts, strengthening soil biological activity, and enhancing plant growth under saline conditions. However, the effectiveness of this technology is strongly influenced by biochar feedstock, pyrolysis temperature, particle size, bacterial strain compatibility, formulation method, and environmental conditions during application. This review concludes that biochar as a carrier for halotolerant bacteria is a promising approach for sustainable saline soil rehabilitation, particularly in marginal lands and coastal areas. Further research is needed to standardize formulations, conduct multi-season field trials, and evaluate technical and economic feasibility at the farmer scale.